Translational genomic research: the role of genetic polymorphisms in MBSR program among breast cancer survivors (MBSR[BC]). Issue 4 (20th August 2018) - Park, Jong Y; Lengacher, Cecile A; Reich, Richard R; Alinat, Carissa B; Ramesar, Sophia; Le, Alice; Paterson, Carly L; Pleasant, Michelle L; Park, Hyun Y; Kiluk, John; Han, Hyo; Ismail-Khan, Roohi; et al.
Abstract : Our data suggests that genetic polymorphisms related to symptoms, and that moderate improvements were attained from participation in the Mindfulness-Based Stress Reduction program for Breast Cancer survivors. Abstract: Genetic variations of breast cancer survivors (BCS) may contribute to level of residual symptoms, such as depression, stress, fatigue, and cognitive impairment. The objective of this study was to investigate whether particular single-nucleotide polymorphisms (SNPs) moderated symptom improvement resulting from the Mindfulness-Based Stress Reduction for Breast Cancer (MBSR[BC]) program. An overarching goal of personalized medicine is to identify individuals as risk for disease and tailor interventions based on genetic profiles of patients with diseases including cancer. BCS were recruited from Moffitt Cancer Center and University of South Florida's Breast Health Program and were randomized to either the 6-week MBSR(BC) program ( n = 92) or Usual Care ( n = 93). Measures of symptoms, demographic, and clinical history data were attained at baseline, 6 weeks, and 12 weeks. A total of 10 SNPs from eight genes known to be related to these symptoms were studied using genomic DNA extracted from blood. Our results were examined for effect sizes, consistency, and statistical significance ( p < .05). Three SNPs (rs4680 in COMT, rs6314 in HTR2A, and rs429358 in APOE) emerged as having the strongest (though relatively weak) and most consistent effects in moderating the impact of the MBSR program on symptom outcomes. Although effects were generally weak, with only one effect withstanding multiple comparisons correction for statistical significance, this translational behavioral research may help start the identification of genetic profiles that moderate the impact of MBSR(BC). The ultimate goal of this study is the development of personalized treatment programs tailored to the genetic profile of each patient.